MANAGEMENT IN THE CONTEXT OF ORGANIZATIONAL DEVELOPMENT - junianto sitorus (Hijri, 2019)
Management is very popular in the world of entre-preneurship and business. Even nowadays, the rich people in the contemporary world are those who are successful in using mana-gement in the organizations they lead. It means management is very important in building and developing organizations. Management becomes a strategic science in determining the direction of an organization development.